Visual Appeal and Emotional Impact on the Audience Interest of Information Systems Students at Universitas Internasional Batam: A Comparison between Anime and Live-Action One Piece in Batam - Kennedy, Kalon; Deli, Deli; Wibowo, Tony (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2025)
This study examines the influence of visual appeal and emotional impact on audience interest in students of Information Systems at Universitas Internasional Batam, using a comparison between the anime and live-action versions of One Piece. The research aims to determine which version—2D anime or 3D live action—has a more significant effect in attracting viewers through visual aesthetics and emotional delivery. A quantitative and qualitative approach was used, involving 271 respondents through a Likert-scale questionnaire. Data were analyzed using SPSS 3, including validity, reliability, normality, multicollinearity, heteroscedasticity, and hypothesis testing. The results indicate that both visual appeal and emotional impact significantly influence audience interest, with emotional impact showing a slightly stronger effect. Additionally, qualitative feedback reveals that anime is favored for its artistic visual and storytelling depth, while live-action is appreciated for its realism and emotional expression. This research provides insights into how different forms of media presentation can affect viewer engagement, which is useful for content creators and media producers.